Slower postnatal motor development in infants of mothers with latent toxoplasmosis during the first 18 months of life - Kaňková, Sárka; Sulc, Jan; Křivohlavá, Romana; Kuběna, Aleš; Flegr, Jaroslav (Early human development, 2012)
Toxoplasmosis, a zoonosis caused by a protozoan, Toxoplasma gondii, is probably the most widespread human parasitosis in developed countries. Pregnant women with latent toxoplasmosis have seemingly younger fetuses especially in the 16th week of gestation, which suggests that fetuses of Toxoplasma-infected mothers have slower rates of development in the first trimester of pregnancy. In the present retrospective cohort study, we analyzed data on postnatal motor development of infants from 331 questionnaire respondents including 53 Toxoplasma-infected mothers to search for signs of early postnatal development disorders. During the first year of life, a slower postnatal motor development was observed in infants of mothers with latent toxoplasmosis. These infants significantly later developed the ability to control the head position (p=0.039), to roll from supine to prone position (p=0.022) and were slightly later to begin crawling (p=0.059). Our results are compatible with the hypothesis that the difference in the rates of prenatal and early postnatal development between children of Toxoplasma-negative and Toxoplasma-positive mothers might be caused by a decreased stringency of embryo quality control in partly immunosuppressed Toxoplasma-positive mothers resulting in a higher proportion of infants with genetic or developmental disorders in offspring. However, because of relatively low return rate of questionnaires and an associated risk of a sieve effect, our results should be considered as preliminary and performing a large scale prospective study in the future is critically needed.
Keywords: vývoj plodu; toxoplazmóza; Child Development; pohybová aktivita; Male; těhotenství; kojenec; parazitární komplikace těhotenství; vývoj dítěte; průzkumy a dotazníky; mužské pohlaví; studie případů a kontrol; Infant; Fetal Development; Toxoplasmosis; Infant, Newborn; ženské pohlaví; novorozenec; Humans; Pregnancy; Surveys and Questionnaires; Pregnancy Complications, Parasitic; Motor Activity; Female; lidé; Case-Control Studies